Case Report: Focal Choroidal Excavation. Issue 3 (March 2021) - Bhakhri, Raman; Yacoub, Robert; Patel, Reena
ABSTRACT: SIGNIFICANCE: Although rarely seen, clinicians should closely monitor patients, especially pregnant patients with focal choroidal excavation (FCE), as it can convert between subtypes and has been linked to pachychoroidal disease and potential for vision loss. PURPOSE: This study aimed to report a case of the conversion of conforming FCE to nonconforming FCE with spontaneous resolution in a pregnant female. CASE REPORT: A 35-year-old Indian woman presented with a slightly decreased vision in the right eye. The patient was 3 months pregnant at this visit. Her ocular history included stable conforming FCE in both eyes that was diagnosed 1 year earlier. Retinal pigmentary changes were noted in both eyes and consistent with previous examinations as being conforming FCEs in both eyes. Optical coherence tomography through the pigmented changes revealed FCE in the right eye with overlying serous fluid, with the left eye showing stable conforming FCE. She was diagnosed with a nonconforming FCE in the right eye secondary to her pregnancy. She was monitored with subsequent visits showing spontaneous resolution of the fluid and conversion back to a conforming FCE. CONCLUSIONS: This case highlights the conversion of a conforming FCE to a nonconforming FCE with spontaneous resolution in a pregnant female. Similarities are seen in terms of pathophysiology with central serous chorioretinopathy, a fellow pachychoroidal disease, which also has pregnancy as a risk factor. Risk factors in pregnant patients such as increased cortisol and increased ocular blood flow may play an important part in the pathophysiology of the conditions, as they both result in choroidal hyperpermeability. Frequent monitoring and follow-up times are suggested for the patients. Lifelong monitoring is also indicated, as reoccurrences have been reported. Further research is needed at this time to elucidate the exact etiology of FCE and conversions between conforming and nonconforming FCE.